2022
DOI: 10.3749/canmin.2200010
|View full text |Cite
|
Sign up to set email alerts
|

The Taxonomy of Mineral Occurrence Rarity and Endemicity

Abstract: Nearly a half of known IMA-approved minerals (as of November 2021) are reported from four localities or fewer and so may be considered rare mineral species. These minerals form a continuum with more common species (e.g., rock-forming minerals), all of which constitute important constituents of Earth and contributors to its dynamics. To better understand the taxonomy of mineral rarity, evaluations have been made on the basis of k-means clustering and kernel density estimation of one-dimensional data on mineral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Urusov [16] explained the gradual drop of symmetry throughout Earth's history as a consequence of an increase in the number of rare (presumably on average of lower symmetry) species of minerals. While this "dissymmetrization" trend is present, and further confirmed by Gavryliv et al [17], it does not explain the root cause for the symmetry decrease. These ideas were further expanded by Urusov [18] with examples of reactions where products have a lower symmetry than the reactant minerals.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Urusov [16] explained the gradual drop of symmetry throughout Earth's history as a consequence of an increase in the number of rare (presumably on average of lower symmetry) species of minerals. While this "dissymmetrization" trend is present, and further confirmed by Gavryliv et al [17], it does not explain the root cause for the symmetry decrease. These ideas were further expanded by Urusov [18] with examples of reactions where products have a lower symmetry than the reactant minerals.…”
Section: Introductionmentioning
confidence: 64%
“…The distinct behavior and impact of common minerals compared to rare ones have been discussed by Hazen and Ausubel [23]. Interestingly, Gavrilyv et al [17] observed that as rarity increases, symmetry indices decrease while the complexity of minerals increases. Although the reciprocal relationship between symmetry indices and mineral complexity is well documented, it has not yet been quantified in the works of Krivovichev and colleagues [21,[25][26][27][28][29].…”
Section: Symmetry Statistics In Different Environments and Timesmentioning
confidence: 93%
“…The context can be present for all categories but essential only for officially regulated mineral and rock names. The historical and social context can be used to trace mineral discoveries' spatial and temporal evolution (Ponomar, in press) that was shown to impact the mineral rarity classification (Gavryliv et al, 2022b). ( 2) Compositional context includes idealized and empirical mineral formulas, ions, elements, impurities, inclusions, and intergrowth material.…”
Section: Discussionmentioning
confidence: 99%
“…The context can be present for all categories but essential only for officially regulated mineral and rock names. The historical and social context can be used to trace spatial and temporal evolution of mineral discoveries (Ponomar, 2023) that was shown to impact the mineral rarity classification (Gavryliv et al, 2022b).…”
Section: Historical and Social Contextmentioning
confidence: 99%
“…Related to these processes are the profound effects of the selection and concentration by water/rock interactions of more than 40 rare elements that collectively represent only 0.01% of crustal atoms in Earth, yet are essential to more than 40% of Earth's mineral diversity-a finding that echoes the observation that most terrestrial minerals are volumetrically trivial and rare (Gavryliv et al, 2022;Hazen & Ausubel, 2016;Hazen et al, 2015;Hystad et al, 2015). Most of these rare-element minerals are not expected on Mars.…”
Section: Comparisons Of Mars and Earth Mineralogymentioning
confidence: 98%